The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5935/abc.20130204
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Abnormalities in Patients with Congenital Heart Disease

Abstract: BackgroundChromosomal abnormalities (CAs) are an important cause of congenital heart disease (CHD).ObjectiveDetermine the frequency, types and clinical characteristics of CAs identified in a sample of prospective and consecutive patients with CHD.MethodOur sample consisted of patients with CHD evaluated during their first hospitalization in a cardiac intensive care unit of a pediatric referral hospital in Southern Brazil. All patients underwent clinical and cytogenetic assessment through high-resolution karyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
5
10
0
4
Order By: Relevance
“…The frequency of chromosomal abnormalities identified in this study was (13.5%) in patients with CHDs associated with PH, 10.8% in patients with CHDs and the overall frequency reported was 12.1% and these results were similar to that found in the studies by Harris et al, 2003, Amorim et al, 2008and Trevisan et al, 2013 who found rates of 12.9-23.1%. But differences observed in relation to the study by Meberg et al, 2000, Bosi et al, 2003, Dadvand et al, 2009and Hartman et al, 2011 found rates of 3-12.1%.…”
Section: Disscusionsupporting
confidence: 90%
See 1 more Smart Citation
“…The frequency of chromosomal abnormalities identified in this study was (13.5%) in patients with CHDs associated with PH, 10.8% in patients with CHDs and the overall frequency reported was 12.1% and these results were similar to that found in the studies by Harris et al, 2003, Amorim et al, 2008and Trevisan et al, 2013 who found rates of 12.9-23.1%. But differences observed in relation to the study by Meberg et al, 2000, Bosi et al, 2003, Dadvand et al, 2009and Hartman et al, 2011 found rates of 3-12.1%.…”
Section: Disscusionsupporting
confidence: 90%
“…Reviewing the literature and identified many studies which evaluated the frequency and types of chromosomal abnormalities reported in patients with congenital heart diseases (whether associated with PH or not) (Meberg et al, 2000;Bosi et al, 2003;Calzolari et al, 2003;Harris et al, 2003;Amorim et al, 2008;Dadvand et al, 2009;Hartman et al, 2011;Trevisan et al, 2013).…”
Section: Disscusionmentioning
confidence: 99%
“…The genetic etiology of CHD is attributed to chromosomal anomalies and single‐gene disorders. Chromosomal anomalies identified through traditional karyotype analysis represent the underlying cause in 3–18% of patients affected by CHD, and the reported prevalence is higher when using techniques such as fluorescence in‐situ hybridization and chromosomal microarray analysis (CMA). Besides chromosomal anomalies, single‐gene disorders, in which gene mutations are associated with syndromic or non‐syndromic cardiac defects, also contribute to CHD.…”
Section: Introductionmentioning
confidence: 99%
“…The main clinical features of aneuploidy disorders include impairments of cognitive development and growth [2,49,50]. More than 30% of individuals with numerical chromosomal abnormalities have cardiac malformations [51][52][53][54].…”
Section: Klinefelter Syndromementioning
confidence: 99%